Implementation of the Jakpreneur Program for MSMEs Fostered by the Sub-Department of Women's Empowerment, Child Protection, and Population Control in Makasar Urban Village, Makasar District - Ilhamsyah Gema Fitrah; Tjitjik Rahaju; Suci Megawati; M Noer Falaq Al Amin (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to describe the implementation of the Jakpreneur Program for MSMEs assisted by the Sub-Department of Community Empowerment, Women and Child Protection, and Population Control (PPAPP), as well as to identify supporting and inhibiting factors in its implementation. This research employs a qualitative approach with a descriptive research type. Data collection techniques include interviews, observations, and documentation, while data analysis uses the Miles and Huberman model consisting of data reduction, data display, and conclusion drawing. The results show that the implementation of the Jakpreneur Program has been carried out fairly well and in accordance with the established policy framework, as analyzed through Edward III’s policy implementation model, which includes communication, resources, disposition, and bureaucratic structure. The communication aspect has been relatively effective and systematic, although limitations remain due to the insufficient number of facilitators. In terms of resources, budget availability, facilities, and authority are generally adequate, but constraints persist in the number of facilitators and participants’ digital literacy. The disposition of implementers reflects a strong commitment, while the bureaucratic structure is supported by clear standard operating procedures, although inter-agency coordination has not yet been fully optimized.